Reanimación protocolizada del shock séptico - Romero P., Carlos; Cornejo R., Rodrigo; Tobar A., Eduardo; Gálvez A., Ricardo; Llanos V., Osvaldo; Castro O., José (Revista Hospital Clínico Universidad de Chile, 2008)
Severe sepsis and septic shock are pathologies with an increasing incidence in the world. Annually, in the USA 200.000 people die because of severe sepsis, the same number that die because of a myocardial infarction, being this last disease much more common. In Chile, a multicentric study found a 40% of prevalence of severe sepsis in critically ill patients, with a mortality of 27%. In this scenario, it becomes of great importance the appropriate and integral management of this condition, by means of an early diagnosis and the implementation of an aggressive protocolized resuscitation, guided by clear goals. During the first stage of the resuscitation cristalloids and/ or colloids can be used, in order to expand the intravascular space, searching for CVP around 8 to 12 mmHg. In case of hypotension refractory to the administration of fluids, it is recommended to start with increasing doses of norepinephrin until a MAP of 65 - 75 mmHg is achieved. The intensity of the septic shock can be stratified according to the requirements of norepinephrine. It is of great importance to obtain blood cultures of the patients and to start with empiric antibiotic therapy as soon as possible. The initial metabolic goal must be the normalization of the central venous oxygen saturation. The implementation of the resuscitation bundle during the first six hours, since the diagnose of severe sepsis is done, increases the chances of surviving. Protocols of sedation and analgesia, and the use of protective mechanical ventilation is highly recommended. The use of hydrocortisone and human ecombinant protein C in selected patients, may have a beneficial result in the outcome. Vasopressin, terlipressin and high-volume hemofiltration can be used as rescue measures for the most severe patients